2005
DOI: 10.1007/s11104-004-0402-5
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur and nitrogen fertility affects flavour of field-grown onions

Abstract: Although glasshouse studies have conclusively demonstrated that S nutrition can affect onion (Allium cepa L.) pungency this has been rarely observed in field-based studies due to difficulties in controlling S nutrition and lack of efficient methods for measurement of flavour bioactives. We have developed a rapid automated method for determination of onion lachrymatory factor ((Z, E)-thiopropanal-S-oxide; LF) based on juice extraction into dichloromethane and gas chromatography (GC) analysis with flame photomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 25 publications
0
25
0
1
Order By: Relevance
“…Moreover, sulphur content in the soil has a great influence on the accumulation of ACSOs, directly affecting flavour and pungency of onion (Randle 1992a,b;Hamilton et al 1997;McCallum et al 2005;Guo et al 2007). Notably, the concentration and lachrymatory factor of thiosulfonates linearly increases as the S content in the soil increases (Randle 1992a;Randle, Bussard 1993;Randle et al 1994), but pungency is not affected by high sulphur content in the soil (Hamilton et al 1997;Lee et al 2009b) and it is not correlated with S level from 16 to 97 p.m. (Yoo et al 2006).…”
Section: Bulb Quality and Biological Propertiesmentioning
confidence: 99%
“…Moreover, sulphur content in the soil has a great influence on the accumulation of ACSOs, directly affecting flavour and pungency of onion (Randle 1992a,b;Hamilton et al 1997;McCallum et al 2005;Guo et al 2007). Notably, the concentration and lachrymatory factor of thiosulfonates linearly increases as the S content in the soil increases (Randle 1992a;Randle, Bussard 1993;Randle et al 1994), but pungency is not affected by high sulphur content in the soil (Hamilton et al 1997;Lee et al 2009b) and it is not correlated with S level from 16 to 97 p.m. (Yoo et al 2006).…”
Section: Bulb Quality and Biological Propertiesmentioning
confidence: 99%
“…For quantitative HPLC analysis of glucose, fructose, sucrose and DP 3-4 fructo-oligosaccharides, ground, freeze-dried tissue (20 mg) was extracted in 1 ml of 80% v/v ethanol by agitation for 15 min at room temperature, centrifuged (13,000·g for 5 min) and filtered through a 0.2 lm Minisart filter. For preliminary HPLC analyses of the C·P12 population, juice extracts were prepared from bulb tissue as described by McCallum et al (2005), diluted by addition of four volumes of ethanol and clarified as above. Carbohydrates in these extracts were fractionated by HPLC on a 220·4.6 mm Applied Biosystems (Foster City, CA, USA) Brownlee amino column and 15·3.2 mm NewGuard amino guard column, on a Waters (Milford, MA, USA) liquid chromatograph (model 626 pump and controller, model 717-plus autosampler).…”
Section: Carbohydrate Analysismentioning
confidence: 99%
“…The composition and total concentrations of ACSOs determine the flavor profile of the plants, differ among Allium species and cultivars (Yoo and Pike, 1998), and vary with the external environment (Randle and Lancaster, 2002). As the direct measurement of the flavor precursors or the active flavor compounds is laborious, technically demanding and costly for large scale routine agronomic or breeding studies (McCallum et al, 2005), enzymatically generated pyruvic acid (EPY) has been used to determine the gross pungency of Allium plants due to the simplicity of the measurement. Early studies showed that the flavor intensity of onion plants correlated well with the levels of EPY in the juice (Schwimmer and Weston, 1961).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that water supply (Freeman and Mossedeghi, 1973), temperature (Randle et al, 1993), harvest time (Bloem et al, 2004), S supply (Randle, 1992;Randle et al, 1999), the amount (Coolong et al, 2004) and the forms of nitrogen (N) supplied (Gamiely et al, 1991), and N and S interactions (Coolong and Randle, 2003;Bloem et al, 2004;McCallum et al, 2005) can affect plant growth, maturity, yield, flavor attributes, and bulb firmness. However, S supply in the substrate is considered to be the primary factor because S is directly involved in the synthesis of the ACSOs and is a major constitutent of the flavor compounds.…”
Section: Introductionmentioning
confidence: 99%